PENGARUH KONFLIK PERAN, KETIDAKJELASAN PERAN, DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR - Catherina Rosally; Yulius Jogi Christiawan (Business Accounting Review, 2016)
The purpose of this study was to collect evidence of three fraud factors which influenced auditor performance. They were conflict role, ambiguity role, and organization commitment at public accountant in Surabaya.Data were obtained by distributing questionnaire and by using multiple regression analysis. The results from this study showed that there were positive significant effect of organization commitment in auditor performance, and negative significant effect of conflict role, ambiguity role in auditor performance.